2012
DOI: 10.1128/jvi.05245-11
|View full text |Cite
|
Sign up to set email alerts
|

The Toll-Like Receptor 3-Mediated Antiviral Response Is Important for Protection against Poliovirus Infection in Poliovirus Receptor Transgenic Mice

Abstract: RIG-I-like receptors and Toll-like receptors (TLRs) play important roles in the recognition of viral infections. However, how these molecules contribute to the defense against poliovirus (PV) infection remains unclear. We characterized the roles of these sensors in PV infection in transgenic mice expressing the PV receptor. We observed that alpha/beta interferon (IFN-␣/␤) production in response to PV infection occurred in an MDA5-dependent but RIG-I-independent manner in primary cultured kidney cells in vitro.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 56 publications
0
79
0
1
Order By: Relevance
“…Several lines of evidence demonstrate that TLR3 plays a role in the antiviral response against enterovirus infections (31)(32)(33)(34)(35)(36)(37). Rhinovirus infection is recognized initially by TLR3 (38).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence demonstrate that TLR3 plays a role in the antiviral response against enterovirus infections (31)(32)(33)(34)(35)(36)(37). Rhinovirus infection is recognized initially by TLR3 (38).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of PV infection, TLR3-mediated type I IFN production is important for viral clearance in vivo 15,16 . In vitro PV infection of splenic DCs promotes type I IFN production in a TLR3-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…TLR3-or TICAM-1-deficient human PV receptor (PVR)-transgenic mice were more susceptible than normal PVR-transgenic mice to intraperitoneal or intravenous inoculation with a low titre of PV 15,16 . TLR3-dependent type I IFN production by splenic CD11c þ DCs and macrophages was essential for the protection of PVR-transgenic mice against PV infection.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using MDA5 Ϫ/Ϫ mice demonstrated that MDA5 signaling is critical for type I IFN induction after virus infection (68,69). MDA5-deficient mice have an increased susceptibility to lethal infection induced by poliovirus (68,69).…”
Section: C Pro Inhibits Mda5-mediated Cellular Defensementioning
confidence: 99%